Zur Vorhersage des Schwindens und Kriechens von normal- und hochfestem Konstruktionsleichtbeton mit Blähtongesteinskörnung - Kvitsel, Vladislav (Karlsruher Reihe Massivbau, Baustofftechnologie, Materialprüfung / Institut für Massivbau und Baustofftechnologie ; Materialprüfungs- und Forschungsanstalt Karlsruhe, 2017)
While the present state of knowledge on the time dependent deformation behaviour of normal and high-strength concrete may be considered as sufficiently determined, the creep and shrinkage of lightweight aggregate (LWA) concrete, particularly of high-strength LWA concrete, can only be specified inadequately. On the basis of the experimental results a prediction model for shrinkage and creep of structural lightweight aggregate concrete was developed.